Efektivitas Metode Peer Teaching dalam Pelatihan Psychological First Aid terhadap Peningkatan Prosocial Behavior Intention Mahasiswa Universitas Nusa Cendana - Irmanuwela Sia; Nicholas Edwin Handoyo; Desi Indriarini; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2025)
Abstract Prosocial behavior, such as helping others, plays a crucial role in supporting mental health, especially among college students who often face psychological challenges and require social support. Psychological First Aid (PFA) is one form of psychosocial support that peers can provide, and peer teaching—where students teach fellow students—is considered an effective method to foster prosocial behavior intentions while enhancing mutual support. This study aimed to evaluate the effectiveness of the peer teaching method in PFA training to increase prosocial behavior intention among students at Nusa Cendana University. A quasi-experimental design with a pre-test–post-test control group was used, involving 88 students grouped through cluster sampling into experimental group I (n=3), experimental group II (n=22), and a control group (n=63). Data were collected online using the Prosocial Tendencies Measure questionnaire and analyzed with repeated measures ANOVA. The results showed no significant differences in pre- and post-test scores across the groups (p-value within subjects = 0.360; between subjects = 0.632). These findings indicate that PFA training using the peer teaching method did not significantly improve prosocial behavior intention. It is recommended that future training incorporate practical field experiences with organizations such as hospitals or disaster response agencies to improve real-world impact.